2015
DOI: 10.3390/w7084511
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Rivers at Risk: Dredging Results in a Loss of Macroinvertebrates. Preliminary Observations from the Narew Catchment, Poland

Abstract: Ecosystem deterioration in small lowland agricultural rivers that results from river dredging entails a significant threat to the appropriate ecohydrological conditions of these water bodies, expressed as homogenization of habitats and loss of biodiversity. Our study was aimed at a comparison of abundance and taxonomic structure of bottom-dwelling macroinvertebrates in dredged and non-dredged stretches of small lowland rivers and tributaries of the middle Narew River, namely: Czaplinianka, Turośnianka, Dąb, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Significant reductions in the density of benthic invertebrates and losses of species typical of slower‐flowing or vegetated reaches have been observed as a consequence of these actions (Cooper et al, ; Grygoruk, Frąk, & Chmielewski, ; Lewis et al, ; Robinson, Newell, Seiderer, & Simpson, ; Szlauer‐Łukaszewska & Zawal, ; Witt, Schroeder, Knust, & Arntz, ). Also, the impacts of dredging have been reported for birds (Howarth, Grant, & Hulbert, ), fishes (Kjelland, Woodley, Swannack, & Smith, ) phytoplankton, periphytic algae (Cabrita, ; Lewis et al, ; Prat et al, ), and diatoms from the epipelic biofilm (Licursi & Gómez, ).…”
Section: Introductionmentioning
confidence: 99%
“…Significant reductions in the density of benthic invertebrates and losses of species typical of slower‐flowing or vegetated reaches have been observed as a consequence of these actions (Cooper et al, ; Grygoruk, Frąk, & Chmielewski, ; Lewis et al, ; Robinson, Newell, Seiderer, & Simpson, ; Szlauer‐Łukaszewska & Zawal, ; Witt, Schroeder, Knust, & Arntz, ). Also, the impacts of dredging have been reported for birds (Howarth, Grant, & Hulbert, ), fishes (Kjelland, Woodley, Swannack, & Smith, ) phytoplankton, periphytic algae (Cabrita, ; Lewis et al, ; Prat et al, ), and diatoms from the epipelic biofilm (Licursi & Gómez, ).…”
Section: Introductionmentioning
confidence: 99%
“…Sudduth and Meyer [31] reported a high number of pollution-tolerant taxa related to urban stream banks in their study. Such a pattern is caused by the regulation of stream banks, leading to the homogeneity of the environment [32,33]. Only an appropriate bioengineering mechanism could slightly increase the abundance of sensitive species [31,34]; however, a lot of other factors also decrease the diversity of urban streams.…”
Section: Macroinvertebratesmentioning
confidence: 99%
“…Grygoruk et al [15] studied the effects of dredging on the benthic macroinvertebrates in agricultural rivers. They demonstrated that the total abundance of riverbed macroinvertebrates in the dredged stretches of the rivers analysed was approximately 70% lower than that in non-dredged areas, and concluded that the dredging of small rivers in agricultural landscapes seriously affects their ecological status by negatively influencing the concentrations and species richness of benthic macroinvertebrates.…”
Section: Contributionsmentioning
confidence: 99%